Diversity and technological potential of yeasts isolated from “coalho” cheese produced in Pernambuco (Research, Society and Development, 2021)
Derived from raw or pasteurized milk, artisanal “coalho” cheese is a food popularly consumed in the Northeast region of Brazil. It presents a microbial diversity of great importance for the dairy industry, as well as the economic and food security aspects. Among the microbiota present in “coalho” cheese are yeasts that currently being highlighted for presenting great potential for application in the food market. In this regard, the present study aimed to isolate, identify and characterize yeasts from “coalho” cheeses produced in three countiens in Pernambuco/Brazil (Arcoverde, Capoeiras and Venturosa). For the identification of yeasts, biochemical and phenotypic tests were used, followed by the characterization of these yeasts in terms of: pathogenicity and diacetyl and β-galactosidase production. The results showed the presence of fifteen yeasts, two from cheese produced in Venturosa and thirteen from cheese produced in Arcoverde. Among these isolates, was possible to identify the genera Dekkera, Pichia, Debaryomyces, Rhodotorula, Saccharomyces, Galactomyces and Candida, the latter being the most prevalent. Some species produced diacetyl, with a higher concentration produced by Pichia minuta. On the other hand, all species produced β-galactosidase, intracellular and extracellular, with Candida versatilis (33.85 U/mL) as the best producer. In addition, according to pathogenicity tests, none of the yeasts poses a risk to human health. With these preliminary results it is possible to conclude that some strains isolated from artisanal “coalho” cheese can have technological potential, however, complementary tests are substantial to propose them to the dairy industry.